Does Religious Proximity Affect FDI Location Choice? An Empirical Analysis of Outward FDI from Morocco to 54 Host Countries - Ait Soussane, Jihad; Mansouri, Dalal; Mansouri, Zahra (Organizations and Markets in Emerging Economies, 2022)
The present paper investigates the effect of religious distance on the choice of location of Moroccan Multinational Enterprises (MNEs) when investing abroad. The main research hypothesis considers the religion as an element of the psychic distance between the home country and host countries that can affect the FDI location decision. The results of the Robust Weighted Least Squares (RWLS) estimation method using panel data of outward FDI flows from Morocco to 54 host countries from 2007 to 2020 show that the more the local Muslim population is important in the host country, the more it receives FDI from Morocco. The results of the study are highly relevant to policymakers as they prove that the religion is important for inward and outward foreign direct investment. On the one hand, policy makers in charge of FDI attractiveness in the host country have to adopt religious strategies accompanied by public–private partnerships to integrate main foreign religions to facilitate the integration of MNEs and reduce their transaction costs. On the other hand, policy makers in charge of promoting outward FDI from the home country have to establish a liaison office in host countries to support the MNEs and facilitate their internationalization process.